A Foreign Body Granuloma of the Buccal Mucosa Induced by Honeybee Sting. (16th March 2017) - Yamamoto, Kazuhiko; Nakayama, Yohei; Matsusue, Yumiko; Kurihara, Miyako; Yagyuu, Takahiro; Kirita, Tadaaki
Abstract : A foreign body granuloma of the buccal mucosa induced by honeybee sting was reported. The patient was an 82-year-old female who presented with a submucous mass at the right buccal mucosa. The mass was 20 mm in diameter, elastically firm, partly mobile without pain or tenderness, and covered with almost normal mucosa. MR image did not delineate the lesion clearly. Under clinical diagnosis of a benign tumor, the lesion was excised under local anesthesia. The excised lesion was14 × 11 × 9   m m in size and solid and yellowish in cut surface. Histologically, the lesion consisted of granulomatous tissue with a few narrow, curved, eosinophilic structures compatible with decomposed fragments of a honeybee sting and was diagnosed as a foreign body granuloma, although the patient did not recall being stung.